Analysis of Factors that Influence the Quality of Life of People Life with HIV/AIDS (PLWHA) in Dr. R. Sosodoro Djatikoesoemo Bojonegoro Hospitals - Ahmad Maftukhin; Nurwijayanti Nurwijayanti; Siti Farida Noor Layla; Byba Melda Suhita (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Background : People with HIV / AIDS need support from the surrounding community, but in reality the opposite is the community's stigma of people with HIV / AIDS is still negative, this has the effect of being isolated from the surrounding community so that the quality of life of people with HIV / AIDS is not optimal. Purpose : The purpose of this study is to analyze the factors that affect the quality of life of people with HIV / AIDS. Methodhs : The design of this study was analytic with cross sectional approach, the population was 427 respondents, the sample size was calculated using the Slovin formula as many as 78 respondents, the type of sampling used was side probabilities with systematic random sampling technique. Results : The results of this study were tested using an ordinal regression test, and the results showed that the significance value of the effect of adherence to ARV consumption on the quality of life of PLWHA was 0.223, nutritional status significance value 0.498 and social support significance value 0.000. So of the three independent variables studied, the effect was only the social support variable because the significance value was below 0.05. Conclusion : factors that affect the quality of life of PLWHA are social support factors